Patients' perspectives on the role of their general practitioner after receiving an advanced cancer diagnosis - Halkett, Georgia; Jiwa, Moyez; Lobb, E. (Wiley-Blackwell Publishing Ltd., 2015)
The aim of this study was to explore patients' perspectives on the role of their general practitioner (GP) after an advanced cancer diagnosis. A qualitative research approach was used. Semi-structured interviews were conducted and data were analysed using a constant comparative methodology. Participants were eligible if they were diagnosed with advanced cancer and referred for palliative radiotherapy. Data saturation was achieved after 21 interviews. Key themes included (1) obtaining diagnosis and referral for advanced cancer treatment; (2) preference for specialist oncology care; (3) a preference for GP to act as an advocate; and (4) obtaining ongoing routine care from their GP. GP involvement in the patients' management was dependent on: time since diagnosis, GP's involvement in diagnosis and referral, doctor/patient relationship, additional chronic conditions requiring management, frequency of seeing oncologist and specialist recommendation to involve GP. Patients want GPs to have varying levels of involvement following an advanced cancer diagnosis. Not all communication between GPs and patients was positive suggesting communication skills training may be a priority. Patients wished to maintain continunity of care for their non-cancer related issues and healthcare of their family members. Future research needs to focus on working with GPs to increase their role in the management of advanced cancer.